SITUAÇÃO EPIDEMIOLÓGICA DA HANSENÍASE E DOS SEUS COMUNICANTES EM CAMPINAS - Carrasco, Maria Angélica Puntel (1993)
Leprosy is a highly prevalent, endemic disease in this country. Due to its long evolution, it gives rise to an extremely important social issue. This paper analyses the epidemiologic status of Leprosy in the municipality of Campinas. The epidemiologic framework indicates that control of leprosy communicants in Campinas remains inefficient, showing the need for further studies upon these social actors, important links in the epidemiologic sequence of this disease.